Threat, drive, and soothe: learning self-compassion in an academic writing retreat. Issue 7 (10th November 2021) - Hammond, Kay
ABSTRACT: As an experienced participant in academic writing retreats, I became aware of conflicting feelings during retreats between ideas of restorative practice and the pressure to produce outputs. Through autoethnographic inquiry, I examined this conflict. I wrote a reflective journal to describe my lived experience of a recent retreat and analysed the text using a self-compassion framework of Gilbert's emotional regulation systems: drive, threat and soothe. Using these three systems as three characters within myself, I explored the influences of the neoliberal university context on my lived experience and sense of my academic identity and well-being. I used these insights to develop a transformed writing identity and practice. I moved from uncritical awareness of my internalisation of neoliberal values of isolation and output, to a more self-nurturing and connected practice. This research offers encouragement to other educators seeking transformative potential through examining their experiences, contexts, identity, and well-being.